Analisis Pemotongan dan Pemungutan PPH Pasal 23 dalam Praktik Perpajakan di Indonesia - Feby Salsabila Dasril; Muhammad Abdillah Pratama Aminullah; Risa Adelila Hasibuan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study is a literature study that aims to analyze the practice of withholding and collecting Income Tax (PPh) Article 23 in the context of tax regulations in Indonesia. Data were obtained through a literature review of laws and regulations, tax textbooks, and relevant scientific journals. The results of the analysis indicate that although the provisions of PPh Article 23 have been regulated in detail, there is still the potential for differences in interpretation in practice, especially regarding the classification of tax objects and withholding rates. This study recommends increasing the socialization of regulations and simplifying tax administration in order to improve taxpayer compliance.